Fabrication of size controllable SU‐8 nanochannels using nanoimprint lithography and low‐pressure thermal bonding methods. (1st February 2014) - Li, Xiaojun; You, Hui; Jiang, Hai; Lin, Ronghui; Kong, Deyi; Jiang, Rui; Zhu, Likai; Gao, Jun; Tang, Min; Wang, Xudi; Fu, Shaojun
Abstract : A new and simple method is demonstrated to achieve size controllable nanochannels by using nanoimprint lithography and low‐pressure thermal bonding methods. The flexible free‐standing SU‐8 allows the bonding of the nanochannels' pattern features at such a low pressure primarily because of 'sequential' bonding made possible by the bonding layer flexibility and the conformal contact made between the bonding layer and the structure layer in a large area. The simple geometrical argument shows that the height of the enclosed nanochannel can be determined by the depth of the cross‐linked SU‐8 trenches as well as by the initial thickness of the thin unexposed SU‐8 layer. The height of the nanochannels can also be controlled by adjusting the ratio of the ridge width to the trench width on the SU‐8 trenches. These simple relationships can serve as a guideline in choosing the parameters for SU‐8 nanochannel fabrication.